Enhancement of Bacillus cereus spore lytic enzyme by a heat-labile non-dialyzable factor in spore extracts - Mencher, Jordan R.; Blankenship, Leroy C. (Biochimica et biophysica acta, 1971)
A heat-labile, non-dialyzable factor has been found in extracts of Bacillus cereus T spores which enhances the murein-solubilizing activity of the spore lytic enzyme apparently by a direct effect on the enzyme.